The Influence of Professional and Pedagogic Competence on Teacher’s Performance - Murkatik, Khodijah; Harapan, Edi; Wardiah, Dessy (Yayasan Sembilan Pemuda Indonesia, 2020)
The world of education continues to be demanded to be able to produce human resources in accordance with the needs of the community and employment in line with the development of technology and culture of the community. This study examines 1) is there an influence of professional competence on teacher performance; 2) is there any influence of pedagogical competence on teacher performance; and 3) is there an influence of professional competence and pedagogical competence together on teacher performance. The results of the study prove both partially and simultaneously there is an influence of professional competence and pedagogical competence on teacher performance. This research contributes to the teacher because the teacher is a very dominant and strategic element in the process of knowledge transfer. Teaching skills are a hallmark of the teaching profession. Achievement of learning goals and success in overcoming learning problems much depends on the ability or competence of teachers.